Propagation of ship induced waves on to the Tanjung Piai coastline - Ab. Razak, Suraya (2008)
Tanjung Piai coastline has been facing critical erosion for years but recently the erosion rate is escalating. Numerical analysis of ship induced waves was carried out to determine the contribution of shipping traffic from Pelabuhan Tanjung Pelepas to the stability of Tanjung Piai coastline. The analysis includes the generation of waves from ships, propagation, transformation from deep water to shallow water and energy formation. Waves generated by ships decrease gradually when it propagate away from the sailing line and then increase near to the shore due to shoaling and damping factor. Bigger waves break near to the shore but smaller waves reach the shore without breaking. Maximum wave height generated by ships at the shoreline is 0.51 meter and the wave period is 3.23 seconds. Wave heights generated by wind were recorded to be between 1.2 and 1.7 meters with periods ranging from 4 to 8 seconds. Energy is related exponentially to wave height and bigger waves form higher energy to the beach. Based on wave energy to the shore, the analyses conducted showed that ship induced waves does not contribute to the erosion at Tanjung Piai coastline because of the small energy formation compare to wind induced waves.